Influence of weather parameters on alternaria leaf blight severity of makhana under the agro-climate of Koshi region of Bihar - SANTOSH KUMAR; MD. NADEEM AKHTAR; SANTOSH KUMAR; MAHESH KUMAR; TRIBHUWAN KUMAR (Journal of Agrometeorology, 2021)
Weather parameters play a pivotal role in the infection process and spread of pathogen. It also influences the expression of susceptibility/resistance of the host plant during post-infection phases. Therefore, an experiment was conducted for two consecutive cropping seasons (2018 &2019) to study the influence of weather parameters such as temperature, humidity, rainfall and wind direction on the emergence of alternaria leaf blight of makhana in Koshi region of Bihar. Maximum per cent disease severity of alternarialeaf blightwas observed during the peak monsoon months (June to August). Highest disease severity of leaf blight (14.80% & 15.7%) was observed in the mid June during crop season, 2018 and 2019. High temperature (36.9oC & 38.1oC), and relative humidity (94% & 96.4%) of both the year 2018 and 2019 were found correlated with higher severity to alternaria leaf blight. Similarly average HTR values (3.1) were also found correlated with the average high temperature and relative humidity of both years (2018 and 2019) in terms of severity of leaf blight disease. Maximum temperatures, relative humidity and rainfall exhibited strong positive linear relationship and influenced the occurrence of alternaria leaf blight disease significantly. We also developed a geo-phytopathological model for the prediction of alternaria leaf blight disease of makhana on the basis of congenial mean temperature and relative humidity.